Zat Pewarna Alam Sebagai Alternatif Zat Warna Yang Ramah Lingkungan - Muhammad Arif Jati (Ornamen, 2004)
Natural colour is colour can be got from in the nature. They are fromplants (wood skin, root, flowers, leaf, fruit, etc), animals, soil, or the other natural materials. Natural colour is known by the people when they lived in the cave. They used it to print on the cave wall, their bodies, their hunt equipments or the others.At glance, natural colour is devided by two, those are synthetic colour arwi natural colour. Both of them have abundant and wekness, depend on the using purposes of each colour.. For example in a synthetic colour is simpler in processing, more variative colour, cheaper price. But in this case, its dump can not be absorpted in the soil, so make a pollution. In a natural calour, it is more difficult and needs much time in processing, its price is so expensive but its dump can not make pollution.Natural colour is taken much from plants, because they are simplest in coLounng matter where in a plant consists more than a kind of colour pigment. And so it has a strong gum power and preservation. It depends on the material will be coloured and the true of its lock material.Keyword  : zat pewama alam